Does vaginal estriol make urodynamic changes in women with overactive bladder syndrome and genitourinary syndrome of menopause?. (March 2018) - Matarazzo, Maria Grazia; Caruso, Salvatore; Giunta, Giuliana; Valenti, Gaetano; Sarpietro, Giuseppe; Cianci, Antonio
Abstract: Objectives: OAB is a common finding in postmenopausal women. Hypoestrogenism is the root cause of many signs and symptoms of Genitourinary Syndrome of Menopause (vaginal dryness, atrophy, dyspareunia, urinary disorders, etc.). As such the aim of this study was to evaluate the urodynamic effects of ultralowdose estriol vaginal gel formulation to treat women with Genitourinary Syndrome of Menopause and Overactive Bladder Syndrome. Study design: This open-labeled, single center, prospective study involved 37 women with OAB recruited in our Urogynecological Unit between January and July 2016. They received estriol 50 mcg/g vaginal gel, one applicator-dose per day for 3 weeks followed by one dose twice a week for 12 weeks. Objective and subjective parameters were evaluated before and after treatment through the urodynamic examination, Overactive Bladder symptom score and Short Form Health Survey-36 questionnaires. Results: Vaginal atrophy symptoms and signs as well as the overactive bladder subjective symptom parameter improved significantly. Urodynamic evaluation showed significant improvement in first desire to void and maximum cystometric capacity after estriol usage. Patients who had detrusor overactivity did not show any improvement for this parameter after treatment. The voiding function parameters did not significantly change. Short form-36 showed a better quality of life after treatment especially for the emotional role, as well as mental and general health. Conclusions: A local ultra-low dose concentration of estriol could be effective in women with vaginal atrophy and Overactive Bladder Syndrome for improving both subjective symptoms and urodynamic parameters of storage function not affecting voiding function.